EFEKTIFITAS EKSTRAK ETANOL DAUN SIRSAK (Annona Muricata L.) TERHADAP KADAR GLUKOSA DARAH TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI ALOKSAN - Najib, Ainun; Tyas Wahyuni, Leny Eka; Hayya, Adieba Warda; Rajab, Alfian Abdul (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Soursop leaves (Annona muricata L.) contain flavonoid compounds. Flavonoid compounds act as diabetes drugs. This study aimed to determine the effect of soursop leaf ethanol extract on alloxan-induced hypoglycemia in white male rats. In this study, four treatment groups were used, namely. negative control received no treatment, positive control received treatment with metformin 9 mg, the first treatment 7.2 mg and the last group was treated with a second dose of 14.4 mg. Rats were satisfied first before being treated, then measured blood sugar levels were. Rats were induced with alloxan intraperitoneally (IP), then observed the development of their blood sugar levels for three days, and their blood sugar levels were checked once a day. For seven days, then given ethanol extract of Soursop leaves daily for five days. The results showed that soursop leaf ethanol extract could reduce blood glucose on days H4-H8, which decreased by 6.67 mg / mL in the treatment group 1 sample and 5.66 mg / mL in the treatment sample.2. The test results with the Kruskal-Wallis test at the level of 0.05 showed that there was no significant difference between the use of soursop leaf ethanol extract and metformin against blood sugar reduction.